2020
DOI: 10.3389/fpsyt.2020.594840
|View full text |Cite
|
Sign up to set email alerts
|

Placing Cognitive Rigidity in Interpersonal Context in Psychosis: Relationship With Low Cognitive Reserve and High Self-Certainty

Abstract: Introduction: People with psychosis show impairments in cognitive flexibility, a phenomenon that is still poorly understood. In this study, we tested if there were differences in cognitive and metacognitive processes related to rigidity in patients with psychosis. We compared individuals with dichotomous interpersonal thinking and those with flexible interpersonal thinking.Methods: We performed a secondary analysis using two groups with psychosis, one with low levels of dichotomous interpersonal thinking (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 53 publications
(81 reference statements)
1
2
0
Order By: Relevance
“…The women with mean menstrual cycles showed less self-certainty, which was also consistent with a reported association between estrogen levels and cycle length [25]. Selfcertainty is a metacognitive construct that has been associated with the emergence and maintenance of delusions [66,67] as well as neurocognitive performance [13] The age at menarche was associated with personalized bias, a cognitive bias directly implicated in the emergence and maintenance of delusions [68,69]. This suggested that women with lower estrogen levels may attribute others with the consequences of negative events.…”
Section: Discussionsupporting
confidence: 84%
“…The women with mean menstrual cycles showed less self-certainty, which was also consistent with a reported association between estrogen levels and cycle length [25]. Selfcertainty is a metacognitive construct that has been associated with the emergence and maintenance of delusions [66,67] as well as neurocognitive performance [13] The age at menarche was associated with personalized bias, a cognitive bias directly implicated in the emergence and maintenance of delusions [68,69]. This suggested that women with lower estrogen levels may attribute others with the consequences of negative events.…”
Section: Discussionsupporting
confidence: 84%
“…It reflects the extent to which the person employs extreme evaluations when judging the self and others. This measure has also been termed dichotomous interpersonal thinking and is considered to be an indicator of cognitive rigidity ( García-Mieres et al, 2020 ). According to Alberts et al (2012) , dichotomous thinking is common in people with EDs.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, PI has a negative impact on the well-being and quality of life of individuals with psychotic disorders [25,26]. Across the entire ACT model of psychopathology, CF and EA are the processes that were most often correlated with the clinical symptoms of schizophrenia [27,28]. CF is characterized by overt and covert behaviors being excessively determined by cognitions, which means that patients struggle with their thoughts, attempt to control them, and have difficulties finding alternative explanations to these thoughts [29].…”
Section: Introductionmentioning
confidence: 99%